Pengaruh Penggunaan Media Alat Peraga Roda Berputar terhadap Hasil Belajar IPA Siswa Kelas V SDN 26 Dompu - Dedi Kusnadi; Titi Pujiarti; Trisno; Dita Aprilia; Mariati; Mulya Yusnarti (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
This research is motivated by yhe lack of effectiveness of applying instructional media in the learning precess so that students are less effetive in understanding the material, seen from the results of the evaluation of learning on theme 7 sub-theme 1 learning 1, the researcher offers a rotating wheel teaching aid that is in accordance with the concrate operational stage so that it gives effect directly to students. The purpose of this study was to find out the effect of using a rotating wheel teaching aid on the science learning outcomes of fifth grade students at SDN 26 Dompu. This research is a type of quantitative research with experimental methods. Data collection techniques in this research are observation, testing, and documentation. Data anality tests, homogeneity ty tests and hypothesis testing. The results showed that based on the results of the researct and discussion, it was concluded that there was an effect of using the rotating wheel teaching aid on the science learning outcomes of fifth grade students at SDN 26 Dompu. This can be seen from the t test whitch shows a sognificant value of 0.001 <0.05, which means there is a significant effect. Furthermore, there is the value of student learning outcomes obtained after the application of the rotating wheel teaching aid to the scinence learning outcome of fifth grade students at SDN 26 Dompu.